La parasitosis y su influencia en el proceso de aprendizaje de los niños y niñas de primero a séptimo año de educación básica de la Escuela “Dolores Veintimilla de Galindo” del cantón San Miguel, parroquia Central, recinto Guapoloma, provincia Bolívar en el periodo lectivo 2010- 2011. - Gaibor Panata, Mónica Alexandra (2011)
know the frequency of intestinal parasitizes and factors of risk in the children from 5 to 14 years of age coming from the enclosure Guapoloma, Parish Central, Canton San Miguel county Bolívar, among August of the 2010 to March 2011, he was carried out a descriptive study of traverse court. I take the data of 35 children, and it foresaw consent he was carried out a survey to obtain information it has more than enough identification data, epidemic antecedents, took samples of grounds and he was carried out the exam direct copro-parasitario, being demonstrated parasitizes in 59% of the sample, prevailing Amoeba hist 31%, and amoeba coli 31%) Without difference according to the sex. The causal opposing agents were. Giardia Lambia in 14%, heminalepis 3%. He was association of intestinal parasitizes and such factors of risk as: Accumulation, inadequate Disposition of the garbage 80%, bad quality of water for the consumption of the water 50%, bad deposit of you excrete them 50%, they don't wash the foods for the consumption 60%, they don't wash his hands after going to the bathroom 40%, they have not received a treatment in the last six months 95%. The association with some considered important variables maybe is due to the homogeneity of the factors of risk in this community. The obtained results of the present investigation will serve as informative source for future investigations and creation of programs of prevention of the intestinal parasitizes and their consequences. Key words: intestinal Parasitosis, Amoeba Hist, Amoeba Coli, Giardia Lambia, Heminalepis